Modified and toughened PET (Polyethylene Terephthalate) endurance plate and preparation method thereof

By introducing polymer prepolymers, toughening modifiers and compatible agents into the PET endurance plate, combining nano-scale inorganic fillers and functional components, and adopting a multi-stage kneading process, the problems of insufficient toughness and poor interfacial compatibility of traditional PET endurance plates are solved, and the high toughness, flame retardancy and weather resistance of the material are improved.

CN119552483AInactive Publication Date: 2025-03-04HUNAN RIJING NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411960446.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PET endurance plates are prone to brittle cracking under high load or complex environmental conditions, lack of toughness, and the molecular chains are prone to degradation during high-temperature processing, resulting in a decrease in material strength. At the same time, PET has poor interfacial compatibility in multi-component blending systems, which often leads to problems such as stratification and performance degradation.

Method used

By introducing polymer prepolymers, toughening modifiers and compatibility agents, branched point or long-link branch structures are formed to improve molecular chain toughness; nano-scale inorganic fillers and functional components are used to improve interface compatibility and flame retardant performance; multi-stage mixing and multi-stage feeding processes are used to ensure uniform fusion of each component and performance synergistic.

Benefits of technology

It significantly enhances the toughness and impact strength of the PET endurance plate, improves the interface compatibility of the multi-component blend system, improves flame retardant and weathering performance, and ensures the stable performance of the material under high temperature and high load conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a modified and toughened PET (polyethylene terephthalate) endurance plate and a preparation method thereof, and relates to the technical field of PET modification, the modified and toughened PET endurance plate is composed of a macromolecular prepolymer, a toughening modifier, a compatilizer, matrix PET resin and a nanoscale inorganic filler; the macromolecular prepolymer is introduced into a branched structure through a modified chain extender, so that the strength and toughness of the matrix are improved; the toughening modifier adopts an elastomer and a functional monomer for graft copolymerization, so that the impact property is improved; the compatilizer is prepared by condensing an oligomer and a surface coupling reagent, so that the interfacial compatibility is improved; the nano filler is subjected to surface modification, so that the impact resistance and thermal stability of the material are enhanced; according to the invention, component synergy is realized through a multi-stage mixing and segmented feeding process, functional components such as a flame retardant and a light stabilizer are further introduced, the flame retardance, weather resistance and aging resistance are remarkably improved, the defects of fragility and multi-component blending interface of traditional PET are overcome, and the composite material is widely applicable to the field of high-performance plastic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PET modification, in particular to a modified and toughened PET endurance board. Background Art

[0002] With the widespread application of modern engineering plastics in the fields of high-performance structural parts and functional products, polyethylene terephthalate (PET) is widely used in the manufacture of endurance sheets due to its excellent mechanical properties, chemical stability and processability; however, traditional PET endurance sheets are prone to brittle cracking under high loads or complex environmental conditions and lack toughness. At the same time, the molecular chains are easily degraded during high-temperature processing, resulting in a decrease in material strength; in addition, PET has poor interfacial compatibility in multi-component blending systems, which often causes problems such as stratification and performance degradation, all of which limit the further promotion of PET endurance sheets in high-end application scenarios. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the deficiencies in the prior art, the present invention provides a modified toughened PET endurance board, which solves the problem of poor comprehensive performance of the prior PET board.

[0005] (II) Technical solution

[0006] To achieve the above-mentioned purpose, in the first aspect, the present application provides a modified toughened PET endurance sheet, and in the second aspect, the present application provides a method for preparing the modified toughened PET endurance sheet; The first technical solution is to provide a modified toughened PET endurance board, which is composed of the following components by mass fraction: 10-25 parts of polymer prepolymer; 5-10 parts of toughening modifier; 3-5 parts of compatibilizer; 60-65 parts of base PET resin; 3-5 parts of nano-scale inorganic filler; The polymer prepolymer is obtained by polyester polycondensation of terephthalic acid and polyol under the condition of modified chain extender; The toughening modifier is prepared by graft copolymerization of an elastomeric material and a monomer containing an active functional group; The compatibilizer is obtained by condensation modification of polyethylene terephthalate oligomer and surface coupling agent under Lewis acid exchange resin catalyst and temperature control conditions; The matrix PET resin has a melt flow rate of 10-20 g / 10 min (measured at 280° C. and 2.16 kg), an inherent viscosity of 0.75-0.85 dl / g, and a crystallinity of not less than 30%; The nano-scale inorganic filler is any one of nano-silicon oxide, nano-layered silicate and modified alumina.

[0007] Preferably, the preparation method of the modified chain extender includes: Step 101, partial pre-reaction: select a monomer containing two or more active functional groups (epoxy, carboxyl or isocyanate), and carry out a partial ring-opening reaction with a polyol at 100-140° C. to output a pre-reaction product; Step 102: condense the obtained pre-reaction product with polyethylene terephthalate at 160-200° C. and under the catalysis of organic tin or titanate to obtain a modified chain extender containing 3-10 branching points; increase the viscosity of the system without chain extension by 10-15%, and reduce the molecular chain degradation rate in subsequent high-temperature extrusion or injection molding.

[0008] It is explained that the modified chain extender can help to increase the molecular weight, stabilize the melt viscosity and reduce processing degradation when reacting with terephthalic acid and polyols to form polyester condensation; the branching points of the modified chain extender form a multi-branch structure on the polyester main chain, which enhances the toughness of the molecular chain under high temperature and tensile conditions; the branched long chains help to disperse stress during extrusion or injection molding, reduce the concentration of free terminal carboxyl groups, and thus reduce the degradation rate; therefore, the modified chain extender, terephthalic acid and polyols are added to the polyester condensation reaction system in a certain proportion to increase the molecular weight of the polyester, stabilize the melt viscosity and reduce processing degradation.

[0009] Preferably, the monomer is a glycidyl ether compound containing 2-4 epoxy groups, such as bisphenol A diglycidyl ether and neopentyl glycol diglycidyl ether; and the polyol is one of ethylene glycol, trimethylolpropane and pentaerythritol.

[0010] Preferably, the preparation of the toughening modifier comprises: Dissolving and mixing: melt the elastomeric material at 120-140°C under the protection of an inert gas (such as nitrogen), add maleic anhydride and azobisisobutyronitrile as a free radical initiator, raise the temperature to 160-200°C, control the pressure to 0.1-0.3MPa, react for 2-4 hours, then cool down, extract and remove the unreacted matter, and dry to obtain a toughening modifier; the elastomeric material is any one of polybutadiene or its modified copolymer, and polyacrylate rubber.

[0011] Preferably, the preparation of the compatibilizer comprises the following steps: Preparation of oligomers: dimethyl terephthalate and polyols (such as ethylene glycol, butanediol) are subjected to transesterification reaction at 140-180°C. When the acid value of the system is reduced to the target range, the reaction is completed. The molecular weight of polyethylene terephthalate oligomer is in the range of 1000-3000, and polyethylene terephthalate oligomer is output; Introducing a surface coupling agent: selecting a surface coupling agent containing a silane group at 100-150° C. and mixing it with a polyethylene terephthalate oligomer in the presence of a Lewis acid exchange resin catalyst; Condensation and modification: Raise the temperature to 160-180°C and maintain for 1-3 hours to allow the coupling group to react with the hydroxyl group in the side chain of the polyethylene terephthalate oligomer to cause an esterification reaction; Post-treatment: remove unreacted small molecules by vacuum distillation or inert gas stripping to obtain a compatibilizer with a surface active group content of ≥0.5wt%.

[0012] The explanation shows that the compatibilizer has good interfacial coupling with the inorganic filler and elastomer components. Through esterification reaction, the functional coupling group is directly bonded to the main chain or side chain of the oligomer, thereby improving its interfacial wetting and adhesion ability in the PET / elastomer / inorganic filler three-phase system, and significantly improving the phase interface defects during multi-component blending.

[0013] Preferably, the nanoscale inorganic filler has an average particle size of no more than 100 nanometers, and after ultrasonic exfoliation and aminosilane treatment, forms a stable micro-nano enhanced structure with the PET matrix under the condition of an average particle size of ≤100 nm; the surface has an aminosilane or acrylsilane functional layer to enhance the interface bonding strength and reinforcement effect with the matrix PET resin, thereby improving the impact strength and heat deformation temperature of the material.

[0014] Preferably, the present invention provides a modified toughened PET endurance board, which further adds 0.5-1.0 parts of a functional component on the basis of the first technical solution, wherein the functional component is any one of a flame retardant and a light stabilizer: The flame retardant includes an organic phosphorus-nitrogen synergistic flame retardant group, and the light stabilizer contains a benzophenone group; The flame retardant is used to form a stable shielding layer with the compatibilizer and the surface groups of the nanofiller during melt blending at 250-280°C, thereby improving the flame retardant performance of the material; The light stabilizer is used to partially bond with the silane group of the compatibilizer to reduce high-temperature volatilization and enhance the ultraviolet shielding effect; It is explained that the light stabilizer and flame retardant undergo esterification / condensation with the silane or titanate groups in the compatibilizer, and synergistically undergo chemical bonding with the modified chain extender, thereby preventing ordinary flame retardants and light stabilizers from volatilizing or decomposing at high temperatures; and undergo coordination in the functional layer on the surface of the nanofiller to form a stable micro-interface composite phase; the micro-interface composite phase reduces the thermal decomposition and volatilization of flame retardants and light stabilizers in a molten state at 250-280°C, and reduces the migration and deposition phenomena that are prone to occur in ordinary PET modified systems, forming a densified flame retardant layer, and blocking excessive flow and dripping of molten PET; the light stabilizer or flame retardant can be fixed / adsorbed on the surface of the nanoparticles to achieve long-term weather resistance or flame retardancy; the traditional approach is simple physical mixing, which is prone to migration and failure.

[0015] Preferably, the functional components are added in stages together with the polymer prepolymer, toughening modifier and compatibilizer in a twin-screw extruder; they are fully dispersed and extruded into pellets under the conditions of a mixing temperature of 230-260°C and a screw speed of 100-200rpm to ensure uniform fusion and performance synergy between the components.

[0016] The second technical solution provides a method for preparing a modified toughened PET endurance sheet, comprising the following steps: Step S001, raw material ratio: prepare the following raw materials according to mass fraction: High molecular weight prepolymer: 10-25 parts; Toughening modifier: 5-10 parts; Compatibilizer: 3-5 parts; Base PET resin: 60-65 parts; Nano-scale inorganic filler: 3-5 parts; Step S002, mixing operation: at 230-240°C, the polymer prepolymer and the matrix PET resin are fully mixed in the main mixing section of the twin-screw extruder; the toughening modifier and the compatibilizer are added in sequence at the secondary feeding port at 220°C; the modified inorganic filler is added in the exhaust section at 210°C, and vacuuming is performed to remove volatile small molecules; after extrusion, pelletizing is performed to obtain modified toughened PET endurance board pellets; Step S003, molding operation: the modified toughened PET endurance board pellets are molded in an injection molding machine, with a barrel temperature of 260-270°C, an injection pressure of 80-150MPa, and a mold temperature of 80-100°C; the molding cycle is 30-60 seconds, and finally a modified toughened PET endurance board is obtained.

[0017] Preferably, the modified toughened PET endurance board is prepared by a multi-stage mixing and multi-stage feeding process, specifically comprising: In the main mixing section (230-240℃), first add the polymer prepolymer and toughening modifier, detect the online torque, and when the viscosity reaches the predetermined value, add the compatibilizer and functional components at the auxiliary feeding port; Nano-scale inorganic fillers are added to the exhaust section and vacuumed to 0.08MPa to minimize filler agglomeration and retain the activity of flame retardants and light stabilizers. The melt obtained is extruded through a die and then pelletized or directly injection molded, avoiding the decomposition of flame retardants, loss of light stabilizers or reduced reaction efficiency of compatibilizers caused by further adding of materials.

[0018] Explanation: The molecular structure and interface coupling are further stabilized by the following methods: the first stage (180-190°C): complete the initial esterification of terephthalic acid and polyols, and add modified chain extenders; the second stage (cooling to 140-150°C): introduce inert gas for stabilization for 30-60 minutes to remove free acid or excess monomers and reduce the side reactions of subsequent functional components; the third stage (heating to 210-220°C): add nanofillers and compatibilizers so that the coupling groups can fully combine with the surface hydroxyl groups of the inorganic filler in this temperature range; temperature-controlled standing (80-100°C): stand and mature for 1-2 hours before melt extrusion or injection molding to further react and cap, slow down high-temperature degradation and maintain the color stability of the finished product.

[0019] (III) Beneficial effects

[0020] The present invention provides a modified toughened PET endurance board, which has the following beneficial effects:

[0021] (1) The present invention introduces a modified chain extender into a polymer prepolymer to form branching points or long chain branching structures on the polyester main chain, significantly enhancing the toughness of the molecular chain under high temperature and tensile conditions; combined with the synergistic effect of the elastomer material and the polar functional group in the toughening modifier, the elongation at break and impact strength of the sheet are further improved, solving the problem of easy brittle cracking of traditional PET endurance sheets.

[0022] (2) The present invention, through the functional design of the compatibilizer, utilizes the chemical bonding between polyethylene terephthalate oligomers and silane-based and titanate-based coupling agents, thereby significantly improving the interfacial wettability and adhesion between the PET matrix and the elastomer and inorganic filler, fundamentally solving the problems of interfacial stratification and uneven performance that are prone to occur in multi-component blending systems.

[0023] (3) The present invention adds functional components to the basic raw materials, and forms a micro-interface composite phase through the synergistic effect of the functional components with the compatibilizer and the functional layer on the surface of the nanofiller. The micro-interface composite phase can effectively reduce the thermal decomposition and volatilization of the components in the high-temperature molten state of 250-280°C, and avoid the migration and deposition problems, thereby ensuring the long-term stability of the flame retardant and weather resistance properties. Through the introduction of functional components, the flame retardant, UV protection and aging resistance properties are simultaneously optimized, showing excellent comprehensive performance.

[0024] (4) The present invention uses segmented feeding and multi-stage mixing processes to enable the modified components to complete the chain extension, toughening and functionalization processes in different temperature ranges in sequence, thereby minimizing processing degradation and by-product accumulation, ensuring melt viscosity stability and processing adaptability, and thus improving the feasibility of endurance sheets in industrial production. DETAILED DESCRIPTION

[0025] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0026] Preparation Example 1-3, used to prepare a polymer prepolymer; Preparation Example 1, the raw material ratio is as follows: Terephthalic acid (TPA)…200g Ethylene glycol (EG)………………120g Modified chain extender (bisphenol A diglycidyl ether)…10g Catalyst (dibutyltin)…0.4g The process steps are: at 150-180°C, TPA and EG are mixed for esterification reaction, and by-product water is removed; After esterification, the temperature was raised to 200°C, and the modified chain extender was added in batches, and the polycondensation was continued for 2 hours until the acid value dropped below 10 mgKOH / g; after cooling, a polymer prepolymer A1 was obtained, which had a molecular weight of about 15,000 and contained 5 branching points.

[0027] Preparation Example 2, the raw material ratio is as follows: Dimethyl terephthalate (DMT)…180g Trimethylolpropane (TMP)…………15g Modified chain extender (neopentyl glycol diglycidyl ether)…8g Titanate catalyst…………………………0.3g The process steps are: completing the transesterification reaction of DMT and TMP at 160°C, and removing the by-product methanol by distillation; A modified chain extender was added, the temperature was raised to 190°C, and polycondensation was continued for about 2 hours to obtain a polymer prepolymer A2.

[0028] Preparation Example 3, the raw material ratio is: Terephthalic acid (TPA)…180g Ethylene glycol…………………………20g Modified chain extender (toluene diisocyanate)...6g Catalyst (dibutyltin)…0.2g The process steps are: esterification reaction is carried out at 150-170°C, and then a chain extender and a catalyst are added; the temperature is raised to 200°C for condensation for 1-2 hours to obtain a polymer prepolymer A3 with a molecular weight of 16,000 and 6 branching points.

[0029] Preparation Example 4-6, used to prepare a toughening modifier; Preparation Example 4, the raw material ratio is as follows: Elastomer material (polybutadiene rubber)…100g Maleic anhydride (MAH)………………2g Free radical initiator (DCP)……………0.5g The process steps are: Under nitrogen protection, the elastomer material was melted at 130°C, and MAH and DCP were added; The temperature was raised to 180°C, maintained for 2 hours, cooled and then extracted to obtain toughening modifier B1.

[0030] Preparation Example 5 is different from Preparation Example 4 in that the elastomeric material is polyacrylate rubber, and toughening modifier B2 is obtained.

[0031] Preparation Example 6 is different from Preparation Example 4 in that the elastomeric material is a hydrogenated styrene-butadiene block copolymer, and the toughening modifier B3 is obtained. The hydrogenated styrene-butadiene block copolymer is a polybutadiene modified copolymer.

[0032] Preparation Example 7-9: used to prepare a compatibilizer; Preparation Example 7, 100 grams of dimethyl terephthalate (DMT) and 60 grams of ethylene glycol (EG) are mixed in a mass ratio of 1:0.6, 2 grams of Lewis acid exchange resin catalyst (such as Amberlyst-15) are added, and the reaction is heated at 140°C for 1 hour, and then the temperature is raised to 180°C for 2 hours. During the transesterification process, the generated methanol is recovered by a condenser to promote the reaction to the direction of generating oligomeric polyester. When the acid value of the system is reduced to below 10 mgKOH / g, the transesterification reaction is completed to obtain a polyethylene terephthalate (PET) oligomer with a number average molecular weight of about 1200. Next, 5 grams of γ-aminopropyltriethoxysilane (APTES) are added to the above PET oligomer, stirred evenly at 100°C, and in the presence of a Lewis acid exchange resin catalyst, the reaction temperature is maintained at 100-150°C for 2 hours to fully mix APTES with the PET oligomer. Subsequently, the reaction system was heated to 160°C and maintained for 3 hours to allow the silane groups in APTES to undergo an esterification reaction with the hydroxyl groups in the side chains of the PET oligomers to form a modified polyester chain extender containing a branched structure. Finally, distillation was performed under reduced pressure (0.05 MPa) to remove unreacted small molecules and by-products, and a compatibilizer C1 with a surface active group content of 0.7 wt% was obtained.

[0033] Preparation Example 8 is different from Preparation Example 7 in that γ-mercaptopropyltriethoxysilane (MPTES) is used as the surface coupling agent instead of APTES to obtain compatibilizer C2.

[0034] Preparation Example 9 is different from Preparation Example 7 in that γ-methacryloxypropyltrimethoxysilane (KH570) is used as a surface coupling agent to obtain a compatibilizer C3.

[0035] Example for preparing modified toughened PET endurance board Example 1, raw material ratio: polymer prepolymer (A1): 15 parts (obtained from Preparation Example 1); Toughening modifier (B1): 7 parts (obtained from Preparation Example 4); Compatibilizer (C1): 3 parts (obtained from Preparation Example 7); Base PET resin: 63 parts; Nano-scale inorganic filler: 3 parts (nano-silicon oxide modified by aminosilane).

[0036] The preparation process is as follows: first add the polymer prepolymer (A1) and the base PET resin (E) into the main mixing section (230-240°C) of the twin-screw extruder and mix them thoroughly; add the toughening modifier (B1) and the compatibilizer (C1) in sequence at the auxiliary feeding port (220°C); add the nano-scale inorganic filler (D1) into the exhaust section (210°C), and evacuate to remove the volatile small molecules; granulation and molding: after extrusion, cool and pelletize, and the pellets are molded in an injection molding machine at a barrel temperature of 260-270°C and a mold temperature of 90°C to obtain a modified toughened PET endurance board, which is recorded as sample 1.

[0037] Example 2, the operation process is the same as Example 1, only the raw material ratio and component type are different, and sample 2 is obtained; Raw material ratio: polymer prepolymer (A2): 12 parts (obtained from Preparation Example 2); toughening modifier (B2): 8 parts (obtained from Preparation Example 5); compatibilizer (C2): 4 parts (obtained from Preparation Example 8); matrix PET resin: 61 parts; nano-scale inorganic filler: 5 parts (treated with modified alumina, particle size ≤100nm).

[0038] Example 3, the operation process is the same as Example 1, only the raw material ratio and component type are different, and sample 3 is obtained; Raw material ratio: polymer prepolymer (A3): 20 parts (obtained from Preparation Example 3); toughening modifier (B3): 5 parts (obtained from Preparation Example 6); compatibilizer (C3): 5 parts (obtained from Preparation Example 9); matrix PET resin: 60 parts; nanoscale inorganic filler: 5 parts (modified layered silicate, particle size ≤100nm).

[0039] Example 4, the operation process is the same as that of Example 1, and the compound toughening modifier is a combination of B1 and B3 to obtain sample 4; Raw material ratio: polymer prepolymer (A1): 15 parts; toughening modifier (B1 and B3 compounded): 10 parts in total (compounded according to B1:B3=6:4); compatibilizer (C2): 4 parts; base PET resin: 63 parts; nano-scale inorganic filler: 3 parts.

[0040] Comparative Example 1, the process is the same as that of Example 1, except that the use of polymer prepolymer and compatibilizer is omitted, and is recorded as Reference 1; In the test example, according to the formulations of Examples 1-4 and Comparative Example 1, mixing and granulation were completed by a twin-screw extruder, and injection molding was used to form test samples.

[0041] Test items include: Tensile strength (MPa): measured in accordance with ASTM D638 standard using an electronic universal testing machine at a test speed of 5 mm / min.

[0042] Elongation at break (%): In the tensile strength test, the elongation at the breaking point was recorded and the average value was taken.

[0043] Impact strength (kJ / m²): Simple supported beam impact test (ISO179) was used, and the sample size was 80mm×10mm×4mm.

[0044] Flame retardant grade (UL-94): According to the UL-94 standard, the vertical burning grade is measured and the best grade among the five groups of samples is selected.

[0045] Yellowing index (ΔYI): After exposure to a xenon lamp aging device for 600 hours, the color change of the sample was measured according to ASTM E313 standard and the performance parameters of the PET board were obtained by testing the samples of Examples 1-4 and Comparative Example 1, as shown in Table 1; Table 1 Performance parameters of PET board in embodiments and comparative examples

[0046] Table analysis: The tensile strength of Examples 1-4 is 72-76MPa, and the elongation at break is more than 115%, which is much higher than that of Comparative Example 1 (60%); it shows that the introduction of the polymer prepolymer effectively improves the matrix strength, and the synergistic effect of the toughening modifier significantly enhances the toughness; the impact strength of the embodiments is 67-70kJ / m², while that of Comparative Example 1 is only 50kJ / m², which further verifies the synergistic effect of the toughening agent and the compatibilizer; the flame retardant grade of Examples 1-4 all reaches V-0, indicating that the flame retardant and the nanofiller synergistically form a dense flame retardant layer, which effectively inhibits the spread of combustion; Comparative Example 1 only reaches V-2, indicating that the flame retardant is difficult to effectively disperse after the interface optimization of the compatibilizer and the functional filler is lacking, affecting the flame retardant effect; the yellowing index of the embodiments is all below 3.5, and the ΔYI of Comparative Example 1 is 7.0, which shows obvious deterioration, indicating that the light stabilizer forms an anti-ultraviolet shielding layer on the sample surface through the synergistic effect with the compatibilizer, which significantly reduces the aging rate.

[0047] Summary: The modified toughened PET endurance board provided by the present invention successfully solves the performance bottleneck of traditional PET endurance board in multi-functional demand scenarios through structural modification of polymer prepolymer, deep grafting of toughening modifier and interface optimization of functionalized compatibilizer, and has significant technical progress and application value.

[0048] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A modified toughened PET endurance board, characterized in that: By mass fraction, it is composed of the following components: 10-25 parts of polymer prepolymer; 5-10 parts of toughening modifier; 3-5 parts of compatibilizer; 60-65 parts of base PET resin; 3-5 parts of nano-scale inorganic filler; The polymer prepolymer is obtained by polyester polycondensation of terephthalic acid and polyol under the condition of modified chain extender; The toughening modifier is prepared by graft copolymerization of an elastomeric material and a monomer containing an active functional group; The compatibilizer is obtained by condensation modification of polyethylene terephthalate oligomer and surface coupling agent under Lewis acid exchange resin catalyst and temperature control conditions; The base PET resin has a melt flow rate of 10-20 g / 10 min, an inherent viscosity of 0.75-0.85 dl / g, and a crystallinity of not less than 30%; The nano-scale inorganic filler is any one of nano-silicon oxide, nano-layered silicate and modified alumina.

2. A modified toughened PET solid sheet according to claim 1, characterized in that: The preparation method of the modified chain extender comprises: Step 101, partial pre-reaction: select a monomer containing two or more active functional groups, and conduct a partial ring-opening reaction with a polyol at 100-140° C. to output a pre-reaction product; Step 102: condense the obtained pre-reaction product with polyethylene terephthalate at 160-200° C. under the catalysis of organic tin or titanate to obtain a modified chain extender.

3. A modified toughened PET solid sheet according to claim 2, characterized in that: The monomer is a glycidyl ether compound containing 2-4 epoxy groups; the polyol is one of ethylene glycol and trimethylolpropane.

4. The modified toughened PET solid sheet according to claim 1, characterized in that: The preparation of the toughening modifier comprises: Dissolving and mixing: melting the elastomeric material at 120-140° C. under the protection of an inert gas, adding maleic anhydride and azobisisobutyronitrile as a free radical initiator, raising the temperature to 160-200° C., controlling the pressure to 0.1-0.3 MPa, reacting for 2-4 hours, cooling down, extracting and removing unreacted substances, and drying to obtain a toughening modifier; the elastomeric material is any one of polybutadiene or its modified copolymer, and polyacrylate rubber.

5. The modified toughened PET solid sheet according to claim 1, characterized in that: The preparation of the compatibilizer comprises the following steps: Carrying out transesterification reaction between dimethyl terephthalate and polyol at 140-180° C., wherein the molecular weight of polyethylene terephthalate oligomer is in the range of 1000-3000, and outputting polyethylene terephthalate oligomer; A surface coupling agent containing a silane group is selected at 100-150° C. and mixed with a polyethylene terephthalate oligomer in the presence of a Lewis acid exchange resin catalyst; Condensation and modification: Raise the temperature to 160-180°C and maintain for 1-3 hours to allow the coupling group to react with the hydroxyl group in the side chain of the polyethylene terephthalate oligomer to cause an esterification reaction; Unreacted small molecules are removed by vacuum distillation or inert gas stripping to obtain a compatibilizer with a surface active group content of ≥0.5wt%.

6. The modified toughened PET solid sheet according to claim 1, characterized in that: The nanometer-scale inorganic filler has an average particle size of no more than 100 nanometers, and after ultrasonic peeling and aminosilane treatment, forms a stable micro-nano enhanced structure with the PET matrix under the condition that the average particle size is ≤100 nm.

7. A modified toughened PET solid sheet according to any one of claims 1 to 6, characterized in that: Add 0.5-1.0 parts of a functional component, wherein the functional component is any one of a flame retardant and a light stabilizer: The flame retardant includes an organic phosphorus-nitrogen synergistic flame retardant group, and the light stabilizer contains a benzophenone group; The flame retardant is used to form a stable shielding layer with the compatibilizer and the surface groups of the nanofiller during melt blending at 250-280°C, thereby improving the flame retardant performance of the material; The light stabilizer is used to partially bond with the silane group of the compatibilizer to reduce high-temperature volatilization and enhance the ultraviolet shielding effect.

8. The modified toughened PET solid sheet according to claim 7, characterized in that: The functional components, high molecular weight prepolymer, toughening modifier and compatibilizer are added in sections in a twin-screw extruder; they are fully dispersed and extruded into pellets under the conditions of a mixing temperature of 230-260° C. and a screw speed of 100-200 rpm.

9. A method for preparing a modified toughened PET endurance sheet, used for preparing the modified toughened PET endurance sheet according to claim 1, characterized in that: The following steps are involved: Step S001, raw material ratio: prepare the following raw materials according to mass fraction: High molecular weight prepolymer: 10-25 parts; Toughening modifier: 5-10 parts; Compatibilizer: 3-5 parts; Base PET resin: 60-65 parts; Nano-scale inorganic filler: 3-5 parts; Step S002, mixing operation: at 230-240°C, the polymer prepolymer and the matrix PET resin are fully mixed in the main mixing section of the twin-screw extruder; the toughening modifier and the compatibilizer are added in sequence at the secondary feeding port at 220°C; the modified inorganic filler is added in the exhaust section at 210°C, and vacuuming is performed to remove volatile small molecules; after extrusion, pelletizing is performed to obtain modified toughened PET endurance board pellets; Step S003, molding operation: the modified toughened PET endurance board pellets are molded in an injection molding machine, with a barrel temperature of 260-270°C, an injection pressure of 80-150MPa, and a mold temperature of 80-100°C; the molding cycle is 30-60 seconds, and finally a modified toughened PET endurance board is obtained.

10. The method for preparing a modified toughened PET solid sheet according to claim 9, characterized in that: The modified toughened PET endurance board is prepared by a multi-stage mixing and multi-stage feeding process, which specifically includes: In the main mixing section (230-240℃), first add the polymer prepolymer and toughening modifier, detect the online torque, and when the viscosity reaches the predetermined value, add the compatibilizer and functional components at the auxiliary feeding port; Nano-scale inorganic fillers are added into the exhaust section and vacuum is applied to 0.08 MPa.

Citation Information

Patent Citations

  • Method of manufacturing polycarbonate / polyester alloy

    CN101367992A

  • Polycarbonate / polyester alloy nano composite material and preparation method thereof

    CN101423656A

  • High-impact-resistance copolyester alloy modification material of sheet for bag and preparation method

    CN109912943A

  • Modified polyester transparent composite material and preparation method thereof

    CN113980436A

Cited By

  • PET (Polyethylene Terephthalate) polyester blade material and blade preparation method

    CN121006037A

  • Flame-retardant cable material based on recycled PET modification and preparation method thereof

    CN121535875A